(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
This study examined the relationship between perception and production difficulties in English pronunciation. The participants were 24 Korean students at California State University, Los Angeles, in the English Language Program. First, the participants were given a listening test, evaluating their ability to discriminate consonants at word, sentence, and passage levels. Second, the participants took a read-aloud test, also at word, sentence and passage levels while they were being recorded. Using binary scoring, the recordings were rated by two raters. The means of perception and production errors observed were then correlated, and the resulting correlation coefficient indicated the kind and degree of relationship between the perception and production errors. The findings showed that although there seem to be differences between the number of perception and production errors, a significant relationship exists between the perception and production difficulties of English pronunciation. The findings of this study inform the ESL teachers and material developers about certain issues that they should consider when planning and designing teaching as well as assessment activities of English pronunciation. Even though this study only focused on perception and production difficulties experienced by Korean students, it can also be used as a reference for our Namibian ESL community in teaching and assessing ESL students.